Derivative Spectrophotometric Estimation of Metformin Hydrochloride and Rosiglitazone Maleate - MANISH BHATIA, NEELA; KASIM MULLANI, ASHISH; SINGHVI, INDRAJEET; SUDESH BHATIA, MANISH (Asian Journal of Chemistry, 2010)
A simple, sensitive and rapid spectrophotometric method has been developed for simultaneous estimation of rosiglitazone maleate and metformin hydrochloride from tablets. Rosiglitazone maleate has absorbance maxima at 316 nm and metformin hydrochloride has absorbance maxima at 232 nm in methanol:water (2:8) mixture. Second derivative ultraviolet spectrophotometric method was used for estimation of metformin hydrochloride and rosiglitazone maleate was estimated directly from its absorbance at 316 nm. This method involves no extraction or separation for estimation of the two drugs. A calibration curve was obtained for metformin hydrochloride by plotting absorbances from the second derivative spectra at 236 nm against the concentration, over a range of 05 to 35 μg/mL in seven mix standards. The slope, intercept and correlation coefficient for this curve were calculated to be 0.0005, -0.0012 and 0.990702, respectively. Similarly, a calibration curve for rosiglitazone maleate was obtained by plotting the absorbance at its sampling wavelength 316 nm against the concentration range of 15 to 105 μg/mL in seven mixed standards. The slope, intercept and correlation coefficient for this curve were calculated to be 0.0087, 0.0332 and 0.997836, respectively. Results of this method were validated statistically and by recovery studies. The results of tablet analysis in terms of percentage of label claim ± standard deviation were 103.54 ± 0.2272 for metformin hydrochloride and 97.6564 ± 2.42413 for rosiglitazone maleate. The percentage recovery ± standard deviation for metformin hydrochloride was 102.53184 ± 2.7839175 and for rosiglitazone maleate was 107.91954 ± 5.3940276.